PEMBERIAN MOBILISASI DINI UNTUK MENURUNKAN RASA NYERI PADA IBU POST SECTIO CAESAREA - Prayoga, Fajar; Yunia, Eva Anita (Akademi Keperawatan Karya Bhakti Nusantara, Magelang, Indonesia, 2025)
Introduction: Sectio caesarea is an operation to help with childbirth through an incision (incision) in the abdominal wall (laparotomy) and uterus (hysterectomy) to deliver the fetus. One of the nursing interventions that can be given is early mobilization for post-operative patients. Mobilization is the main factor in speeding up recovery and preventing post-surgical complications. Early mobilization can increase blood circulation which can reduce pain, prevent thrombophlebitis, provide nutrition for the healing of the wound area and improve smooth kidney function are important goals in the treatment process. These benefits will be felt by patients if they mobilize early after surgery. Method: The research design that will be used is descriptive research. Sampling in this research will use purposive sampling technique. The number of samples that will be used in this research is 2 respondents with cases After Caesarean Section in the inpatient room at TK IV Army Hospital 01.04.07 Pematangsiantar, in April 2024. Results: Based on the results of the implementation that has been carried out, there is a reduction in the intensity of pain in mothers post section caesarea after being given early mobilization techniques Suggestion: Suggestions given for the research that has been carried out are that nurses should be able to innovate in developing nursing knowledge, especially in caring for clients who experience it after caesarean section by providing early mobilization measures to reduce pain in the mother.